Navigating the unseen peril: safeguarding medical imaging in the age of AI - Maertens, Alexandra; Brykman, Steve; Hartung, Thomas; Gafita, Andrei; Bai, Harrison; Hoelzer, David; Skoudis, Ed; Paller, Channing Judith (Frontiers in Artificial Intelligence, 2024)
In response to the increasing significance of artificial intelligence (AI) in healthcare, there has been increased attention – including a Presidential executive order to create an AI Safety Institute – to the potential threats posed by AI. While much attention has been given to the conventional risks AI poses to cybersecurity, and critical infrastructure, here we provide an overview of some unique challenges of AI for the medical community. Above and beyond obvious concerns about vetting algorithms that impact patient care, there are additional subtle yet equally important things to consider: the potential harm AI poses to its own integrity and the broader medical information ecosystem. Recognizing the role of healthcare professionals as both consumers and contributors to AI training data, this article advocates for a proactive approach in understanding and shaping the data that underpins AI systems, emphasizing the need for informed engagement to maximize the benefits of AI while mitigating the risks.